Complete mitogenome of the entomopathogenic fungus Isaria farinosa ARSEF 3. Issue 1 (2nd January 2019) - Zhang, Yong-Jie; Zhang, Shu
Abstract: In this study, the complete mitogenome of an entomopathogenic fungus Isaria farinosa ARSEF 3 was assembled and annotated. This circular mitogenome is 24, 225 bp in length and consists of two rRNA genes ( rnl and rns ), 25 tRNA genes, and 14 standard protein-coding genes of the oxidative phosphorylation system. Only one intron is identified. This group IA intron invades rnl and carries an ORF coding for ribosomal protein S3. Phylogenetic analysis based on concatenated mitochondrial nucleotide sequences confirms I. farinosa in Cordycipitaceae although the taxonomy of strains deposited as I. farinosa in culture collections awaits reappraisal.